Assessing the Use of Continuous-Time and Timed-Triggered Models for Designing Cyber-Physical Systems - Gonçalves, Fernando Silvano; Becker, Leandro Buss (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2014: Anais do IV Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2014)
Different models of computation can be used for designing the embedded computing system from a Cyber-Physical System. Such embedded system should be in charge of executing the control algorithms and communicating with the sensors and actuators. Timed-Trigger and Continuous-Time are examples of models-of-computation (MoC) used in such application domain. This work presents an assessment of using these two MoCs when applied for representing the stability control system from an Unmanned Aerial Vehicle. The paper addresses facilities and difficulties on mapping high-level models using these two MoCs to a typical execution platform.